The Spanish Constitution od 1812 and its reception in Peru: Published in the Revista virtual e-lhr (iustel.com), N.º 14 (June 2012) (RI 412124) - Campos y Fernández de Sevilla, Francisco Javier (2013)
The Cortes of Cádiz ordered on 18 March 1812 that the Constitution were adopted in all the territories subject to the Spanish Crown, and the process for its proclamation were established. We study in this article how the constitution was received and adopted in Lima and finally along the territory of the Viceroyalty of Peru.